Exploring How Anthropomorphic Voices Shape Brand Loyalty Today - Christiarini, Renny; Gautama, Jocky; Putra, Edy Yulianto (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study explores the impact of human-like brand voices on customer loyalty, focusing on how brand trust and affection act as connecting factors, while also considering how worries about privacy can alter the effects in voice assistant interactions. Drawing from surveys of 353 young adults specifically Gen Z and millennials in Indonesia, the results show that viewing a voice assistant as more human-like boosts both trust in the brand and deeper emotional bonds, which in turn strengthen overall loyalty. On top of that, concerns over privacy tend to lessen the positive connection between this human-like perception and trust, highlighting the importance of creating voice assistants that blend relatable human traits with solid privacy protections. Overall, these findings help broaden our understanding of how consumers connect with brands through AI-driven exchanges.